A Planar 2×2 MIMO Antenna Array For 5G Smartphones - Hossain, A K M Zakir; Abd Aziz, Mohamad Zoinol Abidin; Hassim, Nurulhalim; Indra, Win Adiyansyah; Wan Hassan, Wan Haszerila; Herawan, Safarudin Gazali (Science and Information Organization, 2021)
Here, a planar 2×2 MIMO configuration for the 5G smartphone has been presented. A single element modified planar tree profile shape (MPTPS) antenna is implemented to investigate the suitability in future 5G communication for different sub-6 GHz spectrum band. The size of the single MPTPS antenna is 40 × 25 mm2. The electronic band gap (EBG) and partial ground plane (PGP) techniques have been utilized to tune this antenna. The antenna works from 2.81 – 7.23 GHz, with a (VSWR < 2) bandwidth of 4.42 GHz that covers all the midrange sub-6 GHz 5G frequencies. It also has a comparatively good gain of 3.14 dBi, high efficiency of 96% and a bi-directional radiation pattern. The antenna has been implemented in a 145 × 75 mm2 smartphone mainboard with MIMO configuration using polarization diversity. More than -21.1 dB isolation has been found between different ports. A good gain of as high as 6.59 dBi is observed for the MIMO in the band. Also, as MIMO performance, excellent envelope correlation coefficient of less than 0.0029 and minimum diversity gain of 9.9853 has been observed. The investigation has been further stretched by adding a liquid crystal display (LCD) for radiation performance and a hand phantom to assess the performance in terms of specific absorption rate (SAR). It is observed that the SAR value is as low as 0.887641 at 3.5 GHz. This design will motivate the researcher to develop high performance MIMO arrays for 5G smartphones.